Assessing children's incremental word knowledge in the upper primary grades. (October 2021) - Monster, Iris; Tellings, Agnes; Burk, William J.; Keuning, Jos; Segers, Eliane; Verhoeven, Ludo
Word knowledge acquisition is an incremental process that relies on exposure. As a result, word knowledge can broadly range from recognizing the word's lexical status, to knowing its meaning in context, and to knowing its meaning independent of context. The present study aimed to model incremental word knowledge in 1454 upper primary school children from grades 3 to 5 by investigating their abilities on three word knowledge tasks originating from the same set of 300 words: lexical decision, context decision, and definitional decision. A mixed-effects model showed significant differences in performance between tasks and between grades, and a significant interaction indicating that task differences were different for children in grade 5 compared to children in grades 3 and 4. In order to examine further the different task relation patterns at the word level, a cluster analysis was performed using the observed item means, which were corrected for the guessing chance. The analysis showed that for most words, recognition of its lexical status was easier than knowing its meaning in context, which in turn was easier than knowing its meaning independent of context. It is concluded that task relation patterns differ based on mean log frequency as a proxy of word exposure.